Dopamine and Serotonin-Induced Modulation of GABAergic and Glutamatergic Transmission in the Striatum and Basal Forebrain - Momiyama, Toshihiko; Nishijo, Takuma (Frontiers in Neuroanatomy, 2017)
Catecholamine receptor-mediated modulation of glutamatergic or GABAergic transmission in the striatum as well as basal forebrain (BF) has been intensively studied during these two decades. In the striatum, activation of dopamine (DA) D2 receptors in GABAergic terminals inhibits GABA release onto cholinergic interneurons by selective blockade of N-type calcium channels. In the BF, glutamatergic transmission onto cholinergic projection neurons is inhibited via DA D1-like receptors by selective blockade of P/Q-type calcium channels. On the other hand, presynaptic inhibition of the GABA release onto cholinergic neurons mediated by D1-like receptors or 5-HT1B receptors is independent of calcium influx. In addition, the DA receptor-mediated calcium influx dependent presynaptic inhibition mentioned above decreases with postnatal development, with selective coupling between DA receptors and each subtype of calcium channels being unchanged. Furthermore, the precise origin of these GABAergic or glutamatergic inputs to postsynaptic neurons can be identified by recent optogenetic approaches. Thus, modulatory mechanisms in specific synaptic connections between certain types of neurons in the striatum and BF are being identified.